2022
DOI: 10.1007/s00395-022-00953-4
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes from patients with ST-elevation myocardial infarction induce cardioprotection through the purinergic P2Y13 receptor and nitric oxide signaling

Abstract: Red blood cells (RBCs) are suggested to play a role in cardiovascular regulation by exporting nitric oxide (NO) bioactivity and ATP under hypoxia. It remains unknown whether such beneficial effects of RBCs are protective in patients with acute myocardial infarction. We investigated whether RBCs from patients with ST-elevation myocardial infarction (STEMI) protect against myocardial ischemia–reperfusion injury and whether such effect involves NO and purinergic signaling in the RBCs. RBCs from patients with STEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“… 8 , 9 Recent studies using mice with specific deletion of RBC eNOS demonstrated the importance of eNOS signaling in RBCs in blood pressure regulation 10 and myocardial ischemia-reperfusion (I/R). 11 Available data suggest that the cardioprotective factor released from RBCs in the setting of experimental myocardial I/R 4 as well as in patients with acute myocardial infarction 12 is derived from eNOS. However, the signaling downstream of eNOS remains unclear and controversial.…”
mentioning
confidence: 99%
“… 8 , 9 Recent studies using mice with specific deletion of RBC eNOS demonstrated the importance of eNOS signaling in RBCs in blood pressure regulation 10 and myocardial ischemia-reperfusion (I/R). 11 Available data suggest that the cardioprotective factor released from RBCs in the setting of experimental myocardial I/R 4 as well as in patients with acute myocardial infarction 12 is derived from eNOS. However, the signaling downstream of eNOS remains unclear and controversial.…”
mentioning
confidence: 99%
“…1,2 In addition, RBCs have been shown to be physiological regulators of cardiovascular function, especially under hypoxic conditions. [2][3][4] In fact, a recent study demonstrated that RBCs are involved in the regulation of blood pressure. 5 Emerging evidence has revealed that RBCs undergo functional alteration in various cardiovascular and metabolic diseases.…”
mentioning
confidence: 99%
“…In experimental and clinical studies, it has been shown that RBC-derived endothelial nitric oxide synthase (eNOS) provides cardioprotection in acute myocardial infarction (AMI). 1 , 2 , 3 This cardioprotective role of RBCs appears to be mediated at least in part by activation of purinergic signaling via the P2Y 13 receptor and the NO–soluble guanylyl cyclase pathway within the RBCs and protein kinase G in the heart. 1 …”
mentioning
confidence: 99%
“… 1 , 2 , 3 This cardioprotective role of RBCs appears to be mediated at least in part by activation of purinergic signaling via the P2Y 13 receptor and the NO–soluble guanylyl cyclase pathway within the RBCs and protein kinase G in the heart. 1 …”
mentioning
confidence: 99%
See 1 more Smart Citation